Left ventricular thrombus and systemic embolism after painless myocardial infarction in a young female. Issue 2 (March 2018) - Liao, Shao-Feng; Lee, Ching-Hsing; Wu, Lung-Sheng; Li, Chih-Huang; Chen, Hsien-Yi
Oral contraceptives are widely used because of their reliability. Although oral contraceptives are known to increase the risk of thromboembolic events, there are extremely few reports of oral contraceptive–induced left ventricular thrombus. Herein, we report a 37-year-old non-smoking female, who had regularly taken oral contraceptives for 14 years, developed an anterior myocardial infarction concomitant with left ventricular thrombus, bilateral segmental renal infarctions, and lower limb ischemia. Medical treatment with a combination of dual antiplatelet therapy and anticoagulants completely relieved her symptoms.